Deep-water running: a practical review of the literature with an emphasis on biomechanics - Killgore, G. L. (The Physician and Sportsmedicine, 2012)
Deep-water running (DWR) is used as an adjunct to training and conditioning, and as an injury-rehabilitation technique. It is important for the physician or sports medicine practitioner to focus on the underlying physics and biomechanics of running in water in order to better produce the desired physiological, metabolic, and psychological outcomes. Deep-water running maximal heart rate and oxygen consumption values have been consistently shown to be lower than those found during treadmill running. However, recent evidence reveals that there is less of a difference between these maximal values relative to treadmill running and DWR with increased DWR experience. Submaximal values have been shown to be strikingly similar. The skill level of DWR technique, psychological comfort, perception of work, muscular recruitment patterns, and running kinematics are all affected by the physics (ie, temperature, buoyancy, hydrostatic pressure, specific gravity, and drag) of running in water. Therefore, the relationship between the biomechanics and the corollary practical physiological indicators of workload found in DWR must be factored into the appropriate prescription of training and conditioning workloads and rehabilitation protocols.